QT Dispersion is Not Increased in Familial Mediterranean Fever - Topal, F; Tanindi, A; Kurtoglu, HG; Akbulut, S; Kucukazman, M; Topal, FE (Journal of international medical research, 2011)
Familial Mediterranean fever (FMF) is an autoimmune disease inherited as an autosomal recessive trait and is characterized by recurrent attacks of fever and sterile polyserositis. This study examined electrocardiographic ventricular repolarization parameters (QT interval and QT dispersion) in 38 FMF patients and 35 healthy controls. The QT interval was measured manually from the onset of QRS to the end of the T wave (return to the TP baseline). QT dispersion was defined as the difference between the maximum and minimum QT values, and corrected QT was calculated according to the Bazett formula. There were no significant differences between FMF patients and healthy control subjects in any parameter of ventricular repolarization; hence QT dispersion was not affected by FMF. Electrocardiographic assessment of QT interval and QT dispersion are, therefore, of little value for the evaluation of cardiac impairment and risk of arrhythmia in FMF patients.